Low Impact Development Intensive Rural Construction Planning in Xu Fu Village Ningbo, China: Planning Review through Rural Resilience Perspective - Roosmayri Lovina Hermaputi; Chen Hua (Department of Urban and Regional Planning, Diponegoro University, 2017)
Xu Fu Village Ningbo LID Intensive Rural Construction Planning is a cooperation project between Zhejiang University and Ningbo Institute of Technology which named